TiO2:Ce obtido pelo método Pechini modificado para fotodegredação de azo-corante - Vieira, Caroline Gomes de Sousa (2015)
The water contamination has been one of the major problems of society, and various technologies have been recently studied for the treatment of sewage and industrial waste water. Advanced oxidation processes have been studied recently by the satisfactory results in the removal of various organic compounds. To that end, the main objective of this work was to synthesize particles of TiO2 and TiO2 doped with 1 and 2% cerium oxide for application in photocatalysis, using the dye Remazol Yellow Gold (RYG) as a model substrate for testing the photocatalytic activity. For the synthesis of the material was used, modified Pechini method and photocatalysts were heat treated with or without O2 atmosphere at different temperature ranges. The materials were characterized by X-ray diffraction (XRD), infrared spectroscopy (IR) spectroscopy in the visible ultraviolet (UV-Vis) and Raman spectroscopy. The obtained phase, anatase and rutile was very sensitive to the doping and thermal treatment prior to the crystallization process. The pure TiO2 showed a better performance compared to TiO2 doped cerium oxide, and the increase in the dopant concentration led to a decrease in the photocatalytic activity.